A root canal filling per se does not have a significant negative effect on the marginal periodontium. (28th May 2015) - Bertl, Kristina; Suljkanovic, Nedim; Suljkanovic, Lejla; Lettner, Stefan; Esfandeyari, Azadeh; Moritz, Andreas; Stavropoulos, Andreas; Bruckmann, Corinna
Abstract Aim To evaluate the periodontal status of single‐rooted endodontically treated teeth (ET), correcting for patient‐ and tooth‐related factors. Methods Clinical parameters (BoP, PD, CAL) of 240 ET and 240 contralateral vital teeth (VT), before and after non‐surgical periodontal treatment, were extracted retrospectively from the journals of 175 patients. Possible patient‐related (age, gender, smoking status) and tooth‐related (interproximal restoration, root canal filling's extent, post, tooth type) confounders were tested. Results At baseline, frequency of BoP at an interproximal site at ET versus VT was 70.4% versus 65.0%, respectively. The frequency of teeth with interproximal PD ≥5 mm and CAL ≥5 mm was 47.9% versus 42.9% and 54.6% versus 49.6% at ET and VT, respectively. Interproximal PD and CAL at ET versus VT were 3.86 versus 3.61 mm and 4.11 versus 3.95 mm. After correcting for tooth‐related factors, no significant differences were observed between ET and VT. An improper restoration had a significant (p < 0.001) negative effect on BoP [OR 3.49 (95%CI: 1.95–6.27)], PD [36.81% (95%CI: 18.52–57.92)] and CAL [27.01% (95%CI: 12.67–43.18)]. No significant differences between ET and VT were observed regarding clinical outcome of non‐surgical periodontal therapy. Conclusions Presence of a root canal filling per se does not have a significant negative influence on the marginal periodontium, when correcting for the quality of the interproximal restoration.